Insulin and IGF-1 receptor autocrine loops are not required for Exendin-4 induced changes to pancreatic β-cell bioenergetic parameters and metabolism in BRIN-BD11 cells - Rowlands, Jordan; Cruzat, Vinicius; Carlessi, Rodrigo; Newsholme, Philip (Peptides (New York, N.Y. : 1980), 2018)
•Chronic GLP-1R stimulation promotes β-cell metabolic reprogramming.•IGF-1R and IR are important for β-cell development, function and proliferation.•GLP-1 enhanced metabolic phenotype is independent of IR and IGF-1R autocrine loops.•Enhanced metabolism can contribute to GLP-1 pro-survival abilities. Pharmacological long lasting Glucagon-like peptide-1 (GLP-1) analogues, such as Exendin-4, have become widely used diabetes therapies. Chronic GLP-1R stimulation has been linked to β-cell protection and these pro-survival actions of GLP-1 are dependent on the activation of the mammalian target of rapamycin (mTOR) leading to accumulation of Hypoxia inducible factor 1 alpha (HIF-1α). Recent studies from our lab indicate that prolonged GLP-1R stimulation promotes metabolic reprograming of β-cells towards a highly glycolytic phenotype and activation of the mTOR/HIF-1α pathway was required for this action. We hypothesised that GLP-1 induced metabolic changes depend on the activation of mTOR and HIF-1α, in a cascade that occurs after triggering of a potential Insulin-like growth factor 1 receptor (IGF-1R) or the Insulin receptor (IR) autocrine loops. Loss of function of these receptors, through the use of small interfering RNA, or neutralizing antibodies directed towards their products, was undertaken in conjunction with functional assays. Neither of these strategies mitigated the effect of GLP-1 on glucose uptake, protein expression or bioenergetic flux. Our data indicates that activation of IGF-1R and/or the IR autocrine loops resulting in β-cell protection and function, involve mechanisms independent to the enhanced metabolic effects resulting from sustained GLP-1R activation.